Hugo in action : static sites and dynamic jamstack apps - Jain, Atishay (Manning Publications Co., 2022)
Build and deploy a live website in just 30 minutes using Hugo. The Hugo engine lets you rapidly deliver static sites that are low maintenance, high performance, and feature rich. Sometimes, simple is better. Static websites--sites with fixed content--are easier to create and maintain, and inherently more secure than dynamic pages. Hugo in Action is a hands-on guide to using the Hugo static site engine to render these websites in milliseconds. Working with a complete example website and source code samples, you'll learn how to build and host a site that will wow users and stay stable without a third-party server. Full coverage of the Jamstack (Javascript, APIs, Markdown) shows how easy it is to add complex features to super-simple sites, including eCommerce shopping carts, dynamic forms, and multilingual options.